2019
DOI: 10.1167/19.12.21
|View full text |Cite
|
Sign up to set email alerts
|

Misperception of motion in depth originates from an incomplete transformation of retinal signals

Abstract: Depth perception requires the use of an internal model of the eye-head geometry to infer distance from binocular retinal images and extraretinal 3D eye-head information, particularly ocular vergence. Similarly, for motion in depth perception, gaze angle is required to correctly interpret the spatial direction of motion from retinal images; however, it is unknown whether the brain can make adequate use of extraretinal version and vergence information to correctly transform binocular retinal motion into 3D spati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…Accurate perception of MID (both speed and direction) accurately is a complex process that requires integrating extra-retinal (e.g. gaze direction) and retinal information so that 2D information from the retinae are properly mapping to a 3D layout but this transformation can be incomplete (Murdison et al, 2019). It is clear that the differences in temporal errors as a function of speed depended on the angle of approach, as shown in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate perception of MID (both speed and direction) accurately is a complex process that requires integrating extra-retinal (e.g. gaze direction) and retinal information so that 2D information from the retinae are properly mapping to a 3D layout but this transformation can be incomplete (Murdison et al, 2019). It is clear that the differences in temporal errors as a function of speed depended on the angle of approach, as shown in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, speed discrimination thresholds are usually higher for MID than for lateral motion (Aguado & López-Moliner, 2019;Rushton & Duke, 2009)). It has also been shown that differences in perceived speed depend on which part of the retina is stimulated (Brooks & Mather, 2000;Murdison, Leclercq, Lefèvre, & Blohm, 2019) and well known biases in the perceived spatial trajectories (Aguado & López-Moliner, 2019;Harris & Dean, 2003;Lages, 2006;Murdison et al, 2019;Rokers, Fulvio, Pillow, & Cooper, 2018;Welchman, Tuck, & Harris, 2004) or in motion extent in depth (Lages, 2006). The variability in the perception of MID, including speed and direction, makes it worth studying the performance of response timing when dealing with objects moving in depth.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate perception of MID (both speed and direction) is a complex process that requires integrating extra-retinal (e.g., gaze direction) and retinal information so that 2D information from the retinae are properly mapped to a 3D layout, but this transformation can be incomplete 16 . It is clear that the differences in temporal errors as a function of speed depended on the angle of approach, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to lateral motion, speed discrimination thresholds for MID are usually higher 13 , 14 , and prone to individual differences 15 . This is probably because there is an overabundance of available depth cues 16 that makes predictions on timing performance more difficult. When MID is involved, typical monocular cues include optical expansion 17 , shading and texture gradients 18 , 19 , kinetic depth cues and motion parallax, among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation